EXPLORE THE IMPORTANCE OF CREATIVITY AND INNOVATION IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) - Awa, Awa; Palahudin, (Jurnal Visionida, 2023)
Indonesia is a country with a large number of micro, small and medium enterprises (MSMEs) sectors. MSMEs must apply creativity and innovation in order to face increasingly competitive levels of business competition. Understanding and awareness of the importance of creativity and innovation among MSMEs is still low. Understanding the differences between creativity and innovation is still felt to be ambiguous and wrong. The application of the concepts of creativity and innovation is still considered unimportant, considering that many business people want to succeed in their business instantly, without thinking too much, which can drain their mind and energy. The research explores the differences between creativity and innovation, the concept of the importance of creativity and innovation in MSMEs, and the results of research on the importance of creativity and innovation in MSMEs comprehensively examine these things as has never been done before. The aim of the research is to explore the importance of creativity and innovation in MSMEs. The method used is library research, using critical analysis techniques. The results of research exploring the importance of creativity and innovation in MSMEs show that there are 14 differences between creativity and innovation. The importance of creativity and innovation is: (1) creativity and innovation have been accepted in the fields of business/business and management, and can only be achieved through creative and innovative solutions; (2) creativity and innovation in business are two things that business people need to have and develop for success; and (3) creativity and innovation are so important in the business world, that it is necessary to optimize creative and innovative abilities and ideas. Research studies on the importance of creativity and innovation in MSMEs include: the importance of creativity and innovation, the role of creativity and innovation, the impact of creativity and innovation, and the influence of creativity and innovation. The research on the importance of creativity and innovation examines the following 12 things: (1) entrepreneurship (ability, competence, intention, spirit and entrepreneurial mindset); (2) business success/success; (3) continuity/sustainability of business; (4) business development/progress; (5) increasing competitiveness/competitive advantage; (6) buying interest; (7) purchasing decisions; (8) increasing consumer purchasing power; (9) consumer satisfaction; (10) increasing the value of products/services; (11) increase in sales volume/income turnover; and (12) business/marketing performance.